2014
DOI: 10.1002/btpr.1858
|View full text |Cite
|
Sign up to set email alerts
|

Efficient export of prefolded, disulfide‐bonded recombinant proteins to the periplasm by the Tat pathway in Escherichia coli CyDisCo strains

Abstract: Numerous high-value therapeutic proteins are produced in Escherichia coli and exported to the periplasm, as this approach simplifies downstream processing and enables disulfide bond formation. Most recombinant proteins are exported by the Sec pathway, which transports substrates across the plasma membrane in an unfolded state. The Tat system also exports proteins to the periplasm, but transports them in a folded state. This system has attracted interest because of its tendency to transport correctly folded pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 23 publications
1
63
0
Order By: Relevance
“…However, some proteins were exported in an E. coli mutant strain, Δgor/ΔtrxB, that allows formation of the disulfide bonds in the cytoplasm [5]. Similar results were obtained by our group when we expressed disulfide-requiring proteins in 'CyDisCo' (Cytoplasmic Disulfide formation in E. coli) strains that promote efficient formation of disulfide bonds in the cytoplasm [16]. The Tat pathway thus clearly identified these constructs as misfolded in wild type strains and rejected them.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…However, some proteins were exported in an E. coli mutant strain, Δgor/ΔtrxB, that allows formation of the disulfide bonds in the cytoplasm [5]. Similar results were obtained by our group when we expressed disulfide-requiring proteins in 'CyDisCo' (Cytoplasmic Disulfide formation in E. coli) strains that promote efficient formation of disulfide bonds in the cytoplasm [16]. The Tat pathway thus clearly identified these constructs as misfolded in wild type strains and rejected them.…”
Section: Introductionsupporting
confidence: 78%
“…Previous studies [5,16] showed that several disulfide-bonded proteins, including PhoA, a phytase AppA, an scFv construct and a Fab fragment, were exported in E. coli when a Tat signal peptide was present at the N-terminus, provided that disulfide formation could occur in the cytoplasm. In one case this was achieved by expression in Δgor/ΔtrxB cells; this strain passively enables the formation of disulfide bonds in proteins in the cytoplasm by the removal of the two naturally occurring reducing pathways [23].…”
Section: Ifn Hgh An Scfv and A Vh Domain Construct Are All Efficienmentioning
confidence: 99%
See 3 more Smart Citations